Potential of data minimization techniques approach in improving DNA sequences alignment and comparison / Syed Abdul Mutalib Al Junid … [et al.] - Al Junid, Syed Abdul Mutalib; Haron, Muhammad Adib; Abd Majid, Zulkifli; Othman, Zulkifli (Research Management Institute (RMI), 2012)
Nowadays, the demand for advanced and high performance computational method for comparing and searching biological sequences have increased according to exponential growth rate of biological sequences database. Besides this demand, the requirement for high performance and sensitive comparison and alignment tools have also increased after the advantage of the system for defining the solution relates to Deoxyribonucleic Acid (DNA), human genomes and molecular biology figured out through bioinformatics study. Thereby, this research is an attempt to study and investigate the potential of data minimization technique approach in improving the process of aligning and comparing DNA sequences for determine the region of similarity between two or more DNA sequences. Specifically, the research objectives are i) to study various DNA sequences alignment algorithms characteristics, architectures and techniques such as scoring functions, optimal alignment and gap; and ii) to investigate the potential of data minimization approach in minimizing the size of data towards discovering the region of similarity in DNA sequences alignment and comparison and iii) to analyze the optimal sequences alignment properties for molecular biology and bioinformatics application. This study will initially involve algorithm modification, mathematical formulation, logic design and simulation for data minimization and existing DNA sequences alignment algorithm. At the end of the study, it is expecting that we will discover the potential of data minimization technique in minimizing the size of data towards aligning DNA sequences using basic dynamic programming concept.